From health education to digital health literacy – building on the past to shape the future. (December 2021) - Nutbeam, Don
Health education has continuously evolved and taken several distinctive forms over the decades. The emergence of new concepts such as health promotion and health literacy have helped to shape and refine our understanding of how the purpose, content and methods of health education can adapt with to new public health methods and priorities. Viewing health education through the lens of health literacy has been particularly helpful in differentiating between traditional task-focused health education, and skills-focused health education designed to develop more generic, transferable skills. The advent of digital media has enabled unprecedented access to health information but brought with it new challenges. Managing the volume of available information, and assessing its quality and reliability have become essential digital health literacy skills in the information age. As health educators we need to continue to adapt our practices to these new opportunities and understand the challenges that come with them.